The role and impact of Zakat in alleviating stunting by LazisMu DIY Region in Yogyakarta - Satiawan, Andri; Muhammad, Rifqi (Proceeding International Conference on Accounting and Finance, 2024)
The aim of this research is to look at the role of zakat and LazisMu Special Region of Yogyakarta (LazisMu DIY Region) as zakat institutions in managing zakat, especially for stunting alleviation programs. Second, to see the impact that zakat beneficiaries (mustahik) feel with the stunting alleviation program. The population in this research is all parties involved in the Zakat program as an instrument for stunting alleviation by LazisMu DIY Region in 2022. Six people from three different groups were used as a sample: one from the Zakat Institution (LazisMu DIY Region), four mustahik who benefited from the stunting program, and one from the Field Officer (Regional Leadership of the Aisyiyah Special Region of Yogyakarta, or PWA DIY). This is qualitative research, and the data analysis techniques are qualitative descriptive analysis, validity testing (credibility test: data triangulation, transferability test, dependability test, confirmability test), and qualitative data analysis (data reduction, data display, drawing conclusion or verification) to look at the data in this study. The results show that the role of LazisMu DIY Region in distributing zakat funds is very important in efforts to alleviate stunting and has a large positive impact on beneficiaries.